2011
DOI: 10.1177/1363459311425514
|View full text |Cite
|
Sign up to set email alerts
|

‘Oh dear, should I really be saying that on here?’: Issues of identity and authority in an online diabetes community

Abstract: We explore peer-to-peer discussions which took place in a UK-based diabetes 'Virtual Clinic' online community. In particular, we seek to understand the rhetorical nature and content of exchanges over a period of six months from the community's inception. Data were captured weekly and analysis based on thematic discourse analysis. Two key issues emerged regarding how the community shaped the nature of the discussion forum. First, the identity of the forum was established, and boundaries drawn about what was, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 47 publications
(72 reference statements)
2
63
0
Order By: Relevance
“…Consistent with previous research on online support groups in other health conditions [50,53], members used the group to exchange experiences on symptoms and coping. Members particularly discussed anxiety and sadness related to symptoms and illness progression, echoing previous research which has highlighted the fear and uncertainty experienced by those with progressive NMDs [8,9] and the regret associated with declining ability to participate in valued activities [7].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Consistent with previous research on online support groups in other health conditions [50,53], members used the group to exchange experiences on symptoms and coping. Members particularly discussed anxiety and sadness related to symptoms and illness progression, echoing previous research which has highlighted the fear and uncertainty experienced by those with progressive NMDs [8,9] and the regret associated with declining ability to participate in valued activities [7].…”
Section: Discussionmentioning
confidence: 77%
“…In this context, as well as in other health-related online support groups [48,49], self-disclosure was a key factor in developing and maintaining conversations. Most members disclosed their relationship to NMDs in their initial posts, emphasising the importance of this legitimisation when joining such groups [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Survey questions included basic demographic information, eight 5-point Likert scales ranging from [1][2][3][4][5] …”
Section: Sample and Recruitmentmentioning
confidence: 99%
“…Mental health can be enhanced when peer health is present. For example, peer health can improve coping [3], increase psychosocial support [4][5][6][7][8][9][10][11], and decrease diabetes distress [12] by means of shared experiences [7,8,10,13,14]. Peer health can also increase patient knowledge [4,15,16], confidence in diabetes management [17], self-efficacy [12,18,19], and improve glycosylated hemoglobin (A1C) [12,16,[20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that narratives can be used to give advice in a mitigated way, to express support and highlight common ground, to criticize behavior of other participants or to warrant previously made claims (e.g. Armstrong et al 2011;Harrison and Barlow 2009;Kouper 2010;Page 2012;Richardson 2003;Rudolf von Rohr 2015;Sillence 2010;Veen et al 2010). Several studies have indicated how narratives can be used to construct identities, for example as experts, novices, or communities.…”
Section: Theoretical Backdrop: Narratives and Identity Construction Imentioning
confidence: 99%